Hemingway's Geographies Intimacy, Materiality, and Memory - Gruber Godfrey, Laura; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book combines close literary analysis with recent research on culture and the spaces humans inhabit. By examining a wide range of Hemingway's writing, including excerpts from his letters; short stories such as "Big Two-Hearted River" and "On the Quai at Smyrna"; the posthumously-published "The Last Good Country" and A Moveable Feast; and the novels The Sun Also Rises and A Farewell To Arms, Laura Gruber Godfrey shows how characters' immersions in place are essential to Hemingway's fiction. Revising conventional views of Hemingway's various landscapes as literary symbols or external settings for action, Godfrey shows that, for Hemingway, humans and geography are often coextensive and interdependent. .
Introduction: Ernest Hemingway's Intimate Geographies -- Hemingway, the Preservation Impulse, and Cultural Geography -- The Illusion of Remembered Places -- The Radiance of Objects in Place -- Negotiating the Terrain of Conflict -- Afterword -- Works Cited.
Keywords: Literature, Modern-20th century; America-Literatures.; Literature-Philosophy.